Prevalence of hyperemesis gravidarum using the 24-hour pregnancy unique quantification of emesis scale scoring-a descriptive study - Jha, Santosh Kumar; Shrivastava, Veena Rani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Nausea and vomiting occur in 80% of all pregnancies that do not require treatment however; hyperemesis gravidarum (HG), a potentially life-threatening condition affecting 0.3% to 2% of pregnancies, which is characterized by protracted vomiting, retching, severe dehydration, and weight loss (>5% of pre-pregnancy weight) require hospitalization. Methods: This was a hospital based cross-sectional descriptive study done at Kathmandu medical college over duration of 18 months from 1st January 2018 to 30th June 2019. Pregnant women ≤22nd weeks of gestation admitted with nausea and vomiting were taken as study group. Data collection was done with the questionnaire (modified 24 hours pregnancy unique quantification of emesis (PUQE) scoring system) on a structured proforma covering the relevant subjects of the study. Data were analyzed comparing difference in percentages of categorical variables chi-square test. Results: Hundred and forty-nine women were enrolled in this study with nausea vomiting in pregnancy (NVP) among 692 patients of all obstetric admission within 22 weeks of pregnancy. The prevalence of NVP during the study period was 21.67%. Most of the women in the study group belonged to age group of 20-30 years. Only 12% of cases admitted with severe NVP. Mean duration of hospital stay was found to be 2.95±1.86 days. The incidence of the disease was maximum between 7-9 weeks of gestation. Conclusions: There was no significant relation seen in severity of NVP and age, gravidity, education, occupation and BMI of women. Treatment with regular hydration and antiemetic had favourable outcome with early recovery.